EXPLORING THE ROLE OF QUICK COUNT IN ELECTIONS: BETWEEN TRANSPARENCY AND CONTROVERSY - Pabiangan, Netty; Sukardi, Didi; Setiawan, Edy (Fakultas Hukum Universitas Swadaya Gunung Jati, 2024)
Quick count is a method of counting election results that is carried out by taking samples of votes from some polling stations (TPS) to predict the final results of the election. Quick counts have become essential in the democratic process, providing fast and accurate preliminary information about election results and serving as a social control tool that prevents fraud. However, the quick count is also not free from controversy. Some parties doubt the accuracy and independence of the survey institutions that conduct the quick count, given the potential for bias and political pressure. In addition, the quick count results that are different from the official results from the KPU (General Election Commission) can trigger tension and distrust among the public. Therefore, survey institutions must maintain integrity and transparency in implementing quick counts to ensure public trust and legitimacy of the election process.